Positive electrode material and preparation method thereof, positive plate and lithium ion battery
By coating LiPO3-Al(PO3)3 and TiO2-LiF on lithium cobalt oxide material, the problem of performance degradation of lithium cobalt oxide material during high-rate charging and discharging and long-term circulation use is solved, and higher cycle stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411944743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Lithium cobalt oxide materials exhibit performance degradation problems during high-rate charging and discharging and long-term circulation, including irreversible structural phase transformation, electrolyte decomposition and instability of the solid electrolyte interface layer, which affects the safety and service life of the battery.
A two-layer cladding structure is adopted, the first cladding layer is LiPO3-Al(PO3)3 and the second cladding layer is TiO2-LiF, which is coated on lithium cobalt oxide material to stabilize its surface structure, optimize the electron transmission path and enhance its resistance to electrolyte corrosion.
It significantly improves the cycle stability and rate performance of lithium cobalt oxide materials, extends the service life of the battery, and improves the safety of the battery.
Smart Images

Figure CN119905552A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] Lithium cobalt oxide (LiCoO2) is one of the earliest commercially used materials in the field of lithium-ion battery positive electrode materials. With its high theoretical specific capacity and good electrochemical properties, it occupies an important position in many fields such as mobile electronic devices, electric vehicles and energy storage systems.
[0003] However, with the increasing requirements for the performance of lithium-ion batteries, lithium cobalt oxide materials have exposed several limiting factors in commercial applications, especially the increasingly prominent performance degradation problem during high-rate charge and discharge and long-term cyclic use. These problems are mainly manifested in that during continuous charge and discharge, lithium cobalt oxide materials will undergo irreversible structural phase changes, resulting in the gradual attenuation of battery capacity. At the same time, a series of complex side reactions will occur on the surface of lithium cobalt oxide materials, such as electrolyte decomposition and unstable formation of solid electrolyte interface (SEI) layer. These problems not only further aggravate the performance degradation of the material, but also affect the safety and service life of the battery.
[0004] Therefore, it is necessary to develop a positive electrode material that can take into account both battery rate performance and cycle stability. Summary of the invention
[0005] The purpose of the present invention is to provide a positive electrode material to effectively improve the rate performance and cycle stability of a battery in view of the deficiencies of the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A positive electrode material, comprising a lithium cobalt oxide material, a first coating layer coated on the surface of the lithium cobalt oxide material, and a second coating layer coated on the surface of the first coating layer;
[0008] The first coating layer includes LiPO3-Al(PO3)3, and the second coating layer includes TiO2-LiF.
[0009] Among them, the first coating layer LiPO3-Al(PO3)3 and lithium cobalt oxide can effectively stabilize the surface structure of LiCoO2 through the action of covalent bonds, optimize the electron transmission path, and thus improve the cycle stability and rate performance of LiCoO2. The second coating layer TiO2-LiF has fewer holes that can be connected in series, and the holes hinder the flow of electrolyte, thereby resisting the corrosion of the electrolyte, stabilizing the surface structure of LiCoO2, and can cooperate with the first coating layer to further improve the cycle stability and rate performance of lithium cobalt oxide.
[0010] Preferably, the mass ratio of the lithium cobalt oxide material to the first coating layer is 1:0.0004-0.0006. When the mass ratio is too small, the side reaction cannot be reduced and the interface stability cannot be maintained; when the mass ratio is too large, the impedance will increase, which is not conducive to long-term circulation.
[0011] Preferably, the mass ratio of the lithium cobalt oxide material to the second coating layer is 1:0.0001-0.0004. When the mass ratio is too small, the ability to resist electrolyte corrosion will be weakened; when the mass ratio is too large, the transmission of lithium ions will be affected, thereby affecting the electrochemical performance.
[0012] In addition, the present invention also provides a method for preparing a positive electrode material, comprising the following steps:
[0013] Step S1, mixing LiH2PO4 and Al(H2PO4)3 to obtain a mixture A, and adding the mixture A into water to obtain a solution A;
[0014] Step S2, dispersing LiCoO2 into solution A, and obtaining pretreated lithium cobalt oxide after ultrasonic treatment, heating, drying and calcination;
[0015] Step S3, dispersing the lithium cobalt oxide and TiF4 pretreated in step S2 in a solution, and obtaining the positive electrode material after ultrasonic treatment, heating, drying and calcination.
[0016] Preferably, in step S1, in order to obtain a suitable coating amount of the material, the mass ratio of LiH2PO4 to Al(H2PO4)3 is (1-2):1.
[0017] Preferably, in step S2, in order to obtain a suitable coating amount of the material, the mass ratio of mixture A to LiCoO2 is (0.01-0.05):1.
[0018] Preferably, in step S2, the calcination adopts a double-stage temperature to make the coating more uniform. The specific steps of calcination are: first calcining at a high temperature of 280-350°C for 2-3h, and then heating to a high temperature of 550-700°C for 4-6h.
[0019] Preferably, in step S3, in order to obtain a suitable coating amount of the material, the mass ratio of the pretreated lithium cobalt oxide to TiF4 is 1:(0.01-0.05).
[0020] Preferably, in step S3, in order to provide a good coating temperature, the calcination temperature is 700-900° C. and the time is 7-9 hours.
[0021] In addition, the present invention also provides a positive electrode sheet, comprising the positive electrode material mentioned above.
[0022] In addition, the present invention also provides a lithium-ion battery, including a battery core wound by a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell encapsulating the battery core and the electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet.
[0023] Compared with the prior art, the beneficial effect of the present invention is that the present invention synergistically stabilizes the surface structure of LiCoO2 by coating two layers of coating on the outside of lithium cobalt oxide, optimizes the transmission path of electrons, and thus improves the cycle stability and rate performance of lithium cobalt oxide. Among them, LiPO3-Al(PO3)3 as the first coating layer, through the covalent bond between it and lithium cobalt oxide, realizes the effective stabilization of the surface structure of LiCoO2, and also provides a smoother transmission path for electrons, thereby effectively improving the cycle stability and rate performance of LiCoO2 materials; TiO2-LiF as the second coating layer, further optimizes the surface structure and electron transmission path of the positive electrode material on the basis of LiPO3-Al(PO3)3; TiO2-LiF coating layer not only enhances the material's resistance to electrolyte corrosion, but also further stabilizes the surface structure of LiCoO2, providing the battery with higher performance stability and service life. Therefore, through the synergistic effect of these two coating layers, the lithium cobalt oxide positive electrode material of the present invention exhibits excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the positive electrode material of an experimental example of the present invention.
[0025] Among them, 1-lithium cobalt oxide material; 2-first coating layer; 3-second coating layer. DETAILED DESCRIPTION
[0026] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] According to the first aspect of the present application, the present application provides a positive electrode material, including a lithium cobalt oxide material, a first coating layer coated on the surface of the lithium cobalt oxide material, and a second coating layer coated on the surface of the first coating layer; wherein the first coating layer includes LiPO3-Al(PO3)3, and the second coating layer includes TiO2-LiF.
[0028] In some embodiments, the mass ratio of the lithium cobalt oxide material to the first coating layer material is 1:0.0004-0.0006.
[0029] In some embodiments, the mass ratio of the lithium cobalt oxide material to the second coating layer material is 1:0.0001-0.0004.
[0030] In some embodiments, the mass ratio of the first coating layer material to the second coating layer material is 1:0.0001-0.0004.
[0031] According to a second aspect of the present application, the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0032] Step S1, mixing LiH2PO4 and Al(H2PO4)3 to obtain a mixture A, and adding the mixture A into water to obtain a solution A;
[0033] Step S2, dispersing LiCoO2 into solution A, and obtaining pretreated lithium cobalt oxide after ultrasonic treatment, heating, drying and calcination;
[0034] Step S3, dispersing the lithium cobalt oxide and TiF4 pretreated in step S2 in a solution, and obtaining the positive electrode material after ultrasonic treatment, heating, drying and calcination.
[0035] In some embodiments, in step S1, the mass ratio of LiH2PO4 to Al(H2PO4)3 is (1-2):1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1.
[0036] In some embodiments, in step S2, the mass ratio of mixture A to LiCoO2 is (0.01-0.05):1, for example, it can be 0.01:1, 0.02:1, 0.03:1, 0.04:1, or 0.05:1.
[0037] In some embodiments, in step S2, the specific steps of calcination are: first calcining at a high temperature of 280-350°C for 2-3h, and then heating to a high temperature of 550-700°C for calcining for 4-6h.
[0038] In some embodiments, in step S3, the mass ratio of pretreated lithium cobalt oxide to TiF4 is 1:(0.01-0.05), for example, it can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, or 1:0.05.
[0039] In some embodiments, in step S3, the calcination temperature is 700-900°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, and the calcination time is 7-9h, for example, 7h, 8h, 9h.
[0040] According to a third aspect of the present application, the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the above-mentioned positive electrode material.
[0041] According to the fourth aspect of the present application, the present application provides a lithium-ion battery, comprising a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet.
[0042] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil.
[0043] The separator can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0044] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0045] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0046] Experimental Example 1
[0047] (1) Preparation of positive electrode materials:
[0048] like Figure 1 As shown, a positive electrode material provided in this embodiment includes a lithium cobalt oxide material 1 and a first coating layer 2 coated on the outer surface of the lithium cobalt oxide material 1, and a second coating layer 3 coated on the surface of the first coating layer 2, wherein the first coating layer 2 is LiPO3-Al(PO3)3, and the second coating layer 3 is TiO2-LiF.
[0049] The method for preparing the positive electrode material comprises the following steps:
[0050] Step S1, mixing LiH2PO4 and Al(H2PO4)3 in a weight ratio of 1:1 to obtain a mixture A, and adding the mixture A into water to obtain a solution A;
[0051] Step S2, dispersing LiCoO2 into solution A, the mass ratio of LiCoO2 to mixture A being 1:0.01, ultrasonically treating for 35 min, transferring to an oil bath, stirring and heating at 85°C until viscous, taking out, drying completely in a vacuum drying oven, and then placing in a muffle furnace and calcining at 320°C for 2.5 h, and then heating to 720°C and calcining at 5.5 h to obtain pretreated lithium cobalt oxide;
[0052] Step S3, adding the lithium cobalt oxide and TiF4 pretreated in step S2 to an anhydrous ethanol solution in a weight ratio of 1:0.01, ultrasonically treating for 35 minutes, transferring to an oil bath, stirring and heating at 85°C until a viscous state, taking out, drying completely in a vacuum drying oven, and then calcining at 720°C in a muffle furnace for 8.5 hours to obtain the positive electrode material;
[0053] The mass ratio of the lithium cobalt oxide material to the first coating layer material is 1:0.0003, and the mass ratio of the lithium cobalt oxide material to the second coating layer material is 1:0.0001.
[0054] (2) Preparation of positive electrode
[0055] The prepared positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were fully stirred in an N-methyl methyl pyrrolidone solvent system at a mass ratio of 95.5:2.5:2. After being stirred evenly, a positive electrode slurry was obtained, and the slurry was coated on an Al foil, baked, rolled, and slit to obtain a positive electrode sheet.
[0056] (3) Preparation of negative electrode sheet
[0057] Graphite, conductive agent carbon nanotubes, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose were stirred and mixed in deionized water at a mass ratio of 97.2:1.2:0.8:0.8. After being mixed evenly, the negative electrode slurry was coated on Cu foil, baked, rolled, and cut into strips to obtain a negative electrode sheet.
[0058] (4) Preparation of diaphragm
[0059] Polyethylene (PE) polymer film is used as the isolation membrane.
[0060] (5) Preparation of electrolyte
[0061] EC, PP, VC, DEC and PC are mixed uniformly according to the following components and mass ratios to obtain an organic solution, ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 22:25:3:28:22; lithium salt LiPF6 is added to the organic solution, and the mass ratio of the added mass to the organic solution is 9.5:90.5; after uniform mixing, an electrolyte is obtained.
[0062] (6) Preparation of batteries
[0063] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, an electrolyte is injected into the packaging shell and the packaging is performed to finally obtain a lithium-ion battery.
[0064] Experimental Example 2
[0065] The only difference from Experimental Example 1 is that in this Experimental Example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0004.
[0066] The rest is the same as Experimental Example 1 and will not be described again here.
[0067] Experimental Example 3
[0068] The only difference from Experimental Example 1 is that in this Experimental Example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005.
[0069] The rest is the same as Experimental Example 1 and will not be described again here.
[0070] Experimental Example 4
[0071] The only difference from Experimental Example 1 is that in this experimental example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0006.
[0072] The rest is the same as Experimental Example 1 and will not be described again here.
[0073] Experimental Example 5
[0074] The only difference from Experimental Example 1 is that in this Experimental Example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0007.
[0075] The rest is the same as Experimental Example 1 and will not be described again here.
[0076] Experimental Example 6
[0077] The only difference from Experimental Example 1 is that in this experimental example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005, and the mass ratio of lithium cobalt oxide to the second coating layer is 1:0.00005.
[0078] The rest is the same as Experimental Example 1 and will not be described again here.
[0079] Experimental Example 7
[0080] The only difference from Experimental Example 1 is that in this experimental example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005, and the mass ratio of lithium cobalt oxide to the second coating layer is 1:0.0002.
[0081] The rest is the same as Experimental Example 1 and will not be described again here.
[0082] Experimental Example 8
[0083] The only difference from Experimental Example 1 is that in this Experimental Example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005, and the mass ratio of lithium cobalt oxide to the second coating layer is 1:0.0003.
[0084] The rest is the same as Experimental Example 1 and will not be described again here.
[0085] Experimental Example 9
[0086] The only difference from Experimental Example 1 is that in this Experimental Example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005, and the mass ratio of lithium cobalt oxide to the second coating layer is 1:0.0004.
[0087] The rest is the same as Experimental Example 1 and will not be described again here.
[0088] Experimental Example 10
[0089] The only difference from Experimental Example 1 is that in this experimental example, the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005, and the mass ratio of lithium cobalt oxide to the second coating layer is 1:0.0005.
[0090] The rest is the same as Experimental Example 1 and will not be described again here.
[0091] Experimental Example 11
[0092] The only difference from Experimental Example 1 is that this Experimental Example does not contain the second coating layer, and the mass ratio of lithium cobalt oxide to the first coating layer is 1:0.0005.
[0093] The rest is the same as Experimental Example 1 and will not be described again here.
[0094] Experimental Example 12
[0095] The only difference from Experimental Example 1 is that this Experimental Example does not contain the first coating layer.
[0096] The rest is the same as Experimental Example 1 and will not be described again here.
[0097] Experimental Example 13
[0098] The only difference from Experimental Example 1 is that this Experimental Example does not contain the first coating layer and the second coating layer.
[0099] The rest is the same as Experimental Example 1 and will not be described again here.
[0100] Performance Testing
[0101] The lithium-ion batteries prepared in the above Experimental Examples 1-13 were subjected to electrical performance tests at room temperature, with the test conditions being 0.1C for both charge and discharge, and a charge and discharge test voltage range of 3.0 V to 4.60 V. The test results are shown in Table 1 below.
[0102] Table 1
[0103]
[0104]
[0105] From the comparison of the test data of Experimental Examples 1-13 in Table 1 above, it can be seen that when the mass ratio of single-layer coating and double-layer coating is different, the difference in discharge capacity and initial efficiency is not obvious. However, after multiple 100cl room temperature power-on cycles, obvious differences are shown, and the capacity retention rate of lithium cobalt oxide with double-layer coating is higher.
[0106] Among them, Experimental Example 3 with double-layer coated lithium cobalt oxide is the best experimental example and still has a good capacity retention rate after 100cl cycle. This is mainly because the coating amount of Experimental Example 3 effectively improves the cycle stability and rate performance of lithium cobalt oxide, while too much coating amount will affect the deintercalation and transmission of lithium ions, thereby affecting the capacity retention rate after long-term cycling.
[0107] From the comparison of the test data of Experimental Examples 1-10, it can be seen that a too large mass ratio will lead to an overly thick coating layer, thereby affecting the lithium ion transmission pathway of the positive electrode material and reducing the capacity retention rate of long cycles.
[0108] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A positive electrode material, characterized in that: It comprises a lithium cobalt oxide material, a first coating layer coated on the surface of the lithium cobalt oxide material, and a second coating layer coated on the surface of the first coating layer; Wherein, the first coating layer includes LiPO3-Al(PO3)3, and the second coating layer includes TiO2-LiF.
2. The positive electrode material according to claim 1, characterized in that The mass ratio of the lithium cobalt oxide material to the first coating layer is 1:0.0004-0.0006.
3. The positive electrode material according to claim 1, characterized in that The mass ratio of the lithium cobalt oxide material to the second coating layer is 1:0.0001-0.0004.
4. A method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, mixing LiH2PO4 and Al(H2PO4)3 to obtain a mixture A, and adding the mixture A into water to obtain a solution A; Step S2, dispersing LiCoO2 into solution A, and obtaining pretreated lithium cobalt oxide after ultrasonic treatment, heating, drying and calcination; Step S3, dispersing the lithium cobalt oxide and TiF4 pretreated in step S2 in a solution, and obtaining the positive electrode material after ultrasonic treatment, heating, drying and calcination.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S1, the mass ratio of LiH2PO4 to Al(H2PO4)3 is (1-2):
1.
6. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S2, the mass ratio of mixture A to LiCoO2 is (0.01-0.05):
1.
7. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S3, the mass ratio of pretreated lithium cobalt oxide to TiF4 is 1:(0.01-0.05).
8. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S2, the specific steps of calcination are: first calcining at a high temperature of 280-350°C for 2-3h, then heating to a high temperature of 550-700°C for 4-6h; And / or, in step S3, the calcination temperature is 700-900° C. and the time is 7-9 hours.
9. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 3.
10. A lithium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
High-voltage high-energy-density lithium ion battery
CN103311539A
Lithium rich nickel manganese cobalt oxide (LR-NMC)
CN107210419A
Surface-coated modified lithium ion battery high-nickel ternary positive electrode material preparation method and application
CN110611093A
Lithium-ion battery positive pole piece and preparation method thereof
CN112151807A
Multi-element positive electrode material and preparation method thereof, lithium ion battery and electric equipment
CN116864686A